Representing Migration: Analysis of Media Portrayals of Syrian Migrant Women in Turkey - Ruhdan Uzun; Tuğba Asrak Hasdemir (İletişim Kuram ve Araştırma Dergisi, 2017)
The media coverage of women migrations has played an important role in shaping public opinion and governmental policies. This article aims at exploring the media portrayals of Syrian Migrant Women in Turkey. For this purpose, the research data were collected from the three Turkish online newspaper websites, Hürriyet, Birgün and Sabah, each of which has different editorial policy in representing migration, during one year period. The findings of quantitative content analysis of the news stories regarding Syrian migrant women would provide an understanding of the gender dimension of migration in Turkey. It concludes that Syrian Migrant Women in Turkey generally are reported on crime news and are framed as victims or perpetrators. However, the newspapers rarely report their hard living conditions.